Mengembangkan Aktivitas , Kemandirian,Dan Aspek Motorik Halus Menggunakan Model PJBL, Dan Metode Demontrasi, Dengan Kegiatan Kolase Pada Anak Kelompok A - Maulida; Aslamiah (CV. ITTC INDONESIA, 2025)
The problems in this study are the low activity of children in the process of learning activities, the low independence of children in learning activities, and the low ability of the child's fine motor aspects in controlling hand movements that use fine muscles. The approach used is qualitative and the type of Classroom Action Research, carried out with 4 meetings. The setting of this study is the children of group A of the Baitul Makmur Islamic Integrated Early Childhood Education. The results of this study show that the teacher's activities in meeting I scored 9, meeting II scored 12, meeting III got a score of 21, and meeting IV got a score of 24. Children's activities at meeting I received a percentage of 31%, meeting II received a percentage of 50%, meeting III received a percentage of 50%, and meeting IV received 100%. In the activities of the teacher achieve the criteria of very good and the activities of the children achieve the criteria of being very active, the independence of the child achieves a very independent score and the development of fine motor development of the child achieves very good development.